The Role of Primary Schools in Soliciting Parent Involvement in Hulu Langat District - Wee, Jennifer Beng Neo (1995)
This exploratory study examined the role of primary schools in soliciting parent involvement in the Hulu Lanqat district. The role of primary schools was identified via the types of parent involvement activities organised by the schools, and the perceptions of headmasters and teachers on their roles in soliciting parent involvement. The extent of parent involvement in the various activities; the constraints and barriers faced by schools and the perceptions of the headmasters and teachers on the desired extent of parent involvement were also examined. Poportion a testratified cluster sampling was used. to select the subjects. Sample consisted of 119 respondents which comprised 18 head masters, 18 senior assistants (HEM) and 83 teachers who were PIBG committee members. Two sets of instruments were employed. Descriptive statistics using frequency counts and percent ages were used to analyse the data.